Kajian Teoritis Tentang Budaya Organisasi, Independensi, dan Etika Profesi terhadap Kinerja Auditor BPKP melalui Motivasi dan Profesionalisme - Arif Hidayatullah; Siti Maria Wardayati; Ahmad Roziq (Jurnal Akuntansi dan Pajak, 2021)
This study aims to discuss Theoretical Studies of Organizational Culture, Independence, and Professional Ethics on the Performance of BPKP Auditors through Motivation and Professionalism. The factors used include Organizational Culture, Independence, Professional Ethics, Motivation, and Professionalism. This study was conducted to examine the factors that can support the performance of the internal auditors of BPKP. The focus of this research is on the internal auditors of BPKP by using a sampling technique carried out using a questionnaire via google form. This type of research uses a descriptive qualitative method with a theoretical study of the factors that affect the performance of BPKP's internal auditors. The results of this study indicate that: 1) Organizational Culture plays an important role in supporting BPKP Auditor Performance, 2) Professional Ethics plays an important role in supporting BPKP Auditor Performance, 3) Organizational Culture plays an important role in realizing auditor motivation, 4) Professional Ethics plays an important role in supporting Professionalism , 5) Independence plays an important role in supporting BPKP Auditor Performance, 6) Motivation plays an important role in supporting BPKP Auditor Performance, 7) Auditor professionalism plays an important role in supporting BPKP Auditor Performance. From the results of the analysis for the next stage of research development will be carried out statistical tests with SEM analysis.